Genetic Analysis and Functional Study of a Pedigree With Bruck Syndrome Caused by PLOD2 Variant - Wang, Ruo-li; Ruan, Dan-dan; Hu, Ya-nan; Gan, Yu-mian; Lin, Xin-fu; Fang, Zhu-ting; Liao, Li-sheng; Tang, Fa-qiang; He, Wu-bing; Luo, Jie-wei (Frontiers in Pediatrics, 2022)
Abstract Background: Bruck syndrome (BS) is a rare autosomal recessive inherited osteogenesis imperfecta disease characterized by increased bone fragility and joint contracture. The pathogenic gene of type I BS is FKBPl0, whereas that of type II BS is PLOD2. No significant difference has been found in the clinical phenotype between the two types of BS. In this study, we performed genetic analysis of a BS pedigree caused by PLOD2 variant and studied the corresponding cellular function. Methods: Serum biochemistry, parathyroid hormone (PTH), 25-hydroxyvitamin D [25-(OH) D], osteocalcin, and 24-hour urinary calcium levels of a family member with BS was assessed. The genes of the proband were analyzed by second-generation sequencing and exon capture techniques. Sanger sequencing was also performed for the suspected responsible variant of the family member. Wild- and variant-type lentivirus plasmids were constructed by gene cloning and transfected into HEK293T cells. Cell function was verified by real-time quantitative polymerase chain reaction, western blotting, and immunofluorescence detection. Results: In this pedigree, the proband was found to have a homozygous variant c.1856G>A (p. Arg619His) in exon 17 of PLOD2 (NM_182943.3). His consanguineous parents and sisters were p. Arg619His heterozygous carriers. The mRNA expression of PLOD2 in the constructed p. Arg619His variant cells was significantly upregulated, while the expression of PLOD2 and collagen I protein in the cell lysate was significantly downregulated. Immunofluorescence revealed that the wild-type PLOD2 was mainly located in the cytoplasm, and the expression of the PLOD2 protein after c.1856G>A variant was significantly downregulated, with almost no expression, aligning with the western blot results. The serum sodium, potassium, calcium, phosphorus, magnesium, alkaline phosphatase, PTH, 25-(OH) D, osteocalcin, and 24 h urinary calcium levels of the proband, his parents, and sisters were normal. Conclusion: Through gene and cell function analyses, PLOD2 Arg619His missense variant was preliminarily confirmed to cause BS by reducing protein expression.